2014
DOI: 10.5397/cise.2014.17.2.57
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Starting Periods of Passive Exercise on the Clinical Outcome of Arthroscopic Rotator Cuff Repair

Abstract: Background: To compare the effect of different starting periods of rehabilitative exercise (early or delayed passive exercise) on the rate of retear and other clinical outcomes after the arthroscopic repair of the rotator cuff. Methods: In total, 103 patients who underwent arthroscopic repair of the rotator cuff were included in the study. Determined at 2 weeks post-operation, patients who were incapable of passive forward elevation greater than 90˚ were allotted to the early exercise group (group I: 79 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Consequently, arthroscopic rotator cuff repair, a widely accepted treatment for full-thickness rotator cuff tears, is being performed with increasing frequency. 8,37,40 However, despite surgical improvement, the healing failure rate after rotator cuff repair is considerably high (20%-94%). 24,40 Thus, many studies have attempted to identify factors related to healing failure after rotator cuff repair, and several patient-related risk factors have been identified, such as age, preoperative tear size, fatty infiltration, osteoporosis, and tendon quality.…”
mentioning
confidence: 99%
“…Consequently, arthroscopic rotator cuff repair, a widely accepted treatment for full-thickness rotator cuff tears, is being performed with increasing frequency. 8,37,40 However, despite surgical improvement, the healing failure rate after rotator cuff repair is considerably high (20%-94%). 24,40 Thus, many studies have attempted to identify factors related to healing failure after rotator cuff repair, and several patient-related risk factors have been identified, such as age, preoperative tear size, fatty infiltration, osteoporosis, and tendon quality.…”
mentioning
confidence: 99%
“…Rotator cuff tears frequently cause shoulder pain and dysfunction, 10,36 and symptom relief may be expected by anatomic healing of the torn rotator cuffs through surgical repair. 2,36,43 Rotator cuff tears can be classified as partial-thickness and full-thickness rotator cuff tears. Partial-thickness tears are reported to be approximately twice as common as full-thickness tears, 49 with a reported prevalence of 6% to 39%, 6,21,35 and they are frequently symptomatic and may increase in size or progress to fullthickness tears if left untreated.…”
mentioning
confidence: 99%
“…Immobilization for a certain period and proper rehabilitation are important factors for successful clinical results in rotator cuff repair surgery. However, a longer period of immobilization might lead to higher prevalence of stiffness, despite a lower possibility of retear [ 16 ]. It was reported that the prevalence of shoulder stiffness after an arthroscopic rotator cuff repair was usually 10%, and the resistant postoperative stiffness (which is permanent or needs capsular release) was 3.3% to 4.5% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%